2020
DOI: 10.1007/s00134-020-05965-z
|View full text |Cite
|
Sign up to set email alerts
|

Changing care pathways and between-center practice variations in intensive care for traumatic brain injury across Europe: a CENTER-TBI analysis

Abstract: Purpose: To describe ICU stay, selected management aspects, and outcome of Intensive Care Unit (ICU) patients with traumatic brain injury (TBI) in Europe, and to quantify variation across centers.Methods: This is a prospective observational multicenter study conducted across 18 countries in Europe and Israel. Admission characteristics, clinical data, and outcome were described at patient-and center levels. Between-center variation in the total ICU population was quantified with the median odds ratio (MOR), wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…Also, we did not observe any substantial differences in outcome between Victoria, Australia, the UK and Europe, confirming the results of a recent study. (32) Although this could be the result of a homogenous standard of treatment in the three regions, this might also suggest that the differences in therapies may be discordant and urges the need for future studies that study the effect of these therapies in isolation. The IMPACT CT prognostic scheme accounts for only about a third of outcome variance, and outcomes in all three regions may have been affected by unmeasured confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we did not observe any substantial differences in outcome between Victoria, Australia, the UK and Europe, confirming the results of a recent study. (32) Although this could be the result of a homogenous standard of treatment in the three regions, this might also suggest that the differences in therapies may be discordant and urges the need for future studies that study the effect of these therapies in isolation. The IMPACT CT prognostic scheme accounts for only about a third of outcome variance, and outcomes in all three regions may have been affected by unmeasured confounders.…”
Section: Discussionmentioning
confidence: 99%
“…We specifically focused on patients who did not survive their ICU stay. In an earlier publication of Huijben et al [ 13 ], more information on the whole cohort of ICU patients was reported.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a MOR of 2 for outcomes indicates that if two TBI patients with the same injury severity and characteristics presented to two random centers in our sample, one patient will have an over twofold probability of poor outcome. 9,10 Kaplan-Meier survival analysis was performed in 13098 patients with discharge or death time, with patients discharged alive treated as censored data at the time of discharge and subsequently multivariable mixed effect Cox proportional hazards regression was applied to identify the risk factors for survival. To assess for proportionality, we checked if the survival curves crossed for each variable.…”
Section: Introductionmentioning
confidence: 99%